2014
DOI: 10.1016/j.jacc.2013.09.078
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insight Into the Natural History of Short QT Syndrome

Abstract: ObjectivesThis study intends to gain further insights into the natural history, the yield of familial and genetic screening, and the arrhythmogenic mechanisms in the largest cohort of short QT syndrome (SQTS) patients described so far.BackgroundSQTS is a rare genetic disorder associated with life-threatening arrhythmias, and its natural history is incompletely ascertained.MethodsSeventy-three SQTS patients (84% male; age, 26 ± 15 years; corrected QT interval, 329 ± 22 ms) were studied, and 62 were followed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
1
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(182 citation statements)
references
References 20 publications
4
159
1
18
Order By: Relevance
“…35 It is noteworthy that although we postulate that the loss-of-function of the cardiac potassium channels could induce transmission distortion and contribute to female predominance in LQTS, a marked male predominance, up to 80%, has been observed among patients with a short QT syndrome. 36,37 This syndrome is caused by gain-of-function variants in the same channels where loss-of-function variants lead to LQTS, but only in a limited number of cases. It is tempting to suggest a possible role for channel dysfunction in this male predominance, but this must be tempered by the fact that most of the genetic background of this syndrome has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…35 It is noteworthy that although we postulate that the loss-of-function of the cardiac potassium channels could induce transmission distortion and contribute to female predominance in LQTS, a marked male predominance, up to 80%, has been observed among patients with a short QT syndrome. 36,37 This syndrome is caused by gain-of-function variants in the same channels where loss-of-function variants lead to LQTS, but only in a limited number of cases. It is tempting to suggest a possible role for channel dysfunction in this male predominance, but this must be tempered by the fact that most of the genetic background of this syndrome has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…W skrócie, EPS może odegrać rolę u pacjentów z ARVC [113,114] lub DCM [115], natomiast nie przyczynia się do identyfikacji grupy dużego ryzyka wśród pacjentów z HCM (zalecenie klasy III) [116]. W przypadku kanałopatii EPS nie jest wskazane w LQTS [117], CPVT [14] oraz SQTS [118,119], natomiast jego przydatność w zespole Brugadów pozostaje przedmiotem dyskusji [120].…”
Section: Badania Obrazoweunclassified
“…Z SQTS powiązano 5 genów (KCNH2, KCNQ1, KCNJ2, CACNA1C i CACNB2b), ale przydatność przesiewowych badań genetycznych pozostaje mała (w sumie ok. 20% przypadków) [119].…”
Section: Definicje I Epidemiologiaunclassified
“…One proband’s ECG showed that the QTc interval of the patient was shorter than that of healthy controls and characterized with aborted CA, and a novel CACNA1C mutation (p.R1977Q) was first identified in this SQTS patient, but the parents didn’t carry this mutation [115]. However, the roles of p.R1977Q mutation in SQTS are still unknown.…”
Section: Short Qt Syndromesmentioning
confidence: 99%